Faktor Kecelakaan Kerja Dominan yang Terjadi pada Praktik Plumbing - M. Agphin Ramadhan; Febriyani Febriyani; Tuti Iriani (Teknik Sipil Universitas Negeri Padang, 2020)
This study aims to determine the dominant work accident factors that occur in plumbing practice (Case Study in the Builiding Engineering Education Study Program UNJ). This research is a descriptive study using a survey method. The population of this study were the bachelor of Building Engineering Education study program who had implemented plumbing practical course, namely batch 2016 and part of 2017 in total 110 college students who were collected using a questionnaire. Analysis of the test instruments on the validity and reliability obtained reliability results = 0,911. The results of this study indicate that the dominant factors of work accident that occur in plumbing practice is the unsafe action, namely the sub indicators of the used personal protective equipment, work procedure, attitude when working and the used of work equipment above 80%.